(untitled) (BULLETIN OF TARAS SHEVCHENKO NATIONAL UNIVERSITY OF KYIV. ORIENTAL LANGUAGES AND LITERATURES, 2023)
In the review article the theories of the Arabic origin of West European chivalrous poetry were analyzed. The article deals with the problem of the direct interaction between Arabic and European literary traditions, in particular, the probability of the impact of the Arab-Spanish strophic poetry on Provencal troubadour’s lyrics and the possibility of the influence of Andalusian poetry on Spanish and Provencal. So that it is established that al-Andalus was a multilingual society in which the Andalusi Romance dialects were spoken and written alongside Arabic. In Europe, and from scholars working in departments of modern national languages, this usually means the discussion of what it means to write in Middle English, or German, or French instead of Latin. The Andalusian poets could easily convey in Romance the motives and themes inherent in Arabic classical literature, and with the help of the Arabic language they expressed elements of Roman folk poetry. The analysis of various researches showed that the issue of the historical and geographical formation and development of Arab-Spanish poetry during the Middle Ages were studied by Arab and European sceintists of past centuries, as well as by the modern literary scientists. Modern studies of the Arab-Spanish medieval stanza do not deny the existence of an interaction between European and Arabic lyrics, but the role of this interaction on the scale of the history of world literature remains unclear. Lyrics of the troubadours of the 11th–14th centuries was a unique synthesis of many literary elements of church Latin poetry, folk poetry and Arab influences, and strongly influenced on the history of Italian, Spanish, English, Portuguese, German literature.